Development of a semi-industrial multi fruit dryer system using simultaneous intelligent control - Javanmard, Marjan; Endan, Johari; Abbas, Kassim Ali; Arvin, Farshad (Science Publications, 2010)
Problem statement: This study presented a semi-industrial fruit dryer machine which is useful to dry different types of fruit. The drying process and its functions are selectable by user to obtain a multi dryer system. Approach: A microcontroller base controller that enables to simultaneous monitoring was utilized. There are two types of sensors as the inputs of system which are temperature and humidity. The output of sensors continuously was monitored with the main processor and given functions based on fruit types are executed. The selected fruits were put on trays in batch dryer. Results: Presented system was tested on three different fruits which have differences in texture and moisture content. The optimum drying temperature where provided because the product would be dried without burning. The material moisture content decreased throughout the drying process. A cause study was done to illustrate the effectiveness of the designed dryer. Conclusion: Several performed results illustrated the amenability of proposed system as the multi-fruit dryer machine.